Pengaruh Pengetahuan Akuntansi, Pemanfaatan Teknologi Digital, Dan Kompetensi Sumber Daya Manusia Terhadap Kredibilitas Laporan Keuangan UMKM Di Kota Surakarta - Tara Elisa Putri; Sri Isfantin Puji Lestari; Dwinda Agustintia (JURNAL ILMIAH EDUNOMIKA, 2026)
The credibility of financial statements plays an important role in supporting business sustainability, particularly for Micro, Small, and Medium Enterprises (MSMEs). Credible financial reports provide reliable information that can be used by business owners and external stakeholders in making economic decisions. This study aims to examine the influence of accounting knowledge, digital technology utilization, and human resource competence on the credibility of MSME financial statements in Surakarta City. The study adopted a quantitative approach using primary data collected through questionnaires distributed to 100 MSME owners selected through purposive sampling. Data were analyzed using multiple linear regression with IBM SPSS Statistics. The findings indicate that accounting knowledge and human resource competence have a positive and significant effect on the credibility of financial statements. Conversely, digital technology utilization does not significantly affect financial statement credibility, indicating that the adoption of digital accounting applications among MSMEs remains relatively low. Simultaneously, accounting knowledge, digital technology utilization, and human resource competence significantly influence the credibility of MSME financial statements. The model explains 54.8% of the variation in financial statement credibility. These findings imply that improving accounting literacy and strengthening human resource competence are essential to producing more credible financial reports among MSMEs.